Reactive Arthritis After Intravesical Bacillus Calmette-Guérin Therapy. Issue 2 (March 2022) - Taniguchi, Yoshinori; Nishikawa, Hirofumi; Kimata, Takahito; Yoshinaga, Yasuhiko; Kobayashi, Shigeto; Terada, Yoshio
Abstract : Abstract: Reactive arthritis (ReA) is a sterile arthritis that occurs in genetically predisposed individuals secondary to an extra-articular infection, usually of the gastrointestinal or genitourinary tract. Sterile arthritis associated with instillation of intravesical bacillus Calmette-Guérin (iBCG) therapy used for bladder cancer can also be included under ReA based on the pathogenic mechanism. Similar to spondyloarthritis, HLA-B27 positivity is a known contributor to the genetic susceptibility underlying iBCG-associated ReA. Other genetic factors, such as HLA-B39 and HLA-B51, especially in Japanese patients, can also be involved in the pathophysiology of iBCG-associated ReA. The frequencies of ReA- and ReA-related symptoms are slightly different between Japanese and Western studies. Proper understanding of possible complications, their epidemiology and pathogenesis, and their management is important for the rheumatologist when noting symptomatic patients using iBCG. Herein, we will review the most current information on ReA after iBCG therapy.